“We All Used to Meet at the Hall”: Assessing the Significance of the Universal Negro Improvement Association in Toronto, 1900–1950 - Marano, Carla (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2014)
This article discusses the unique factors that led the UNIA in Toronto to become a central fixture in the city’s black community and to the Garvey movement as a whole. Beginning in 1919, the Toronto Division served as a secular outlet for blacks in the city to express their concerns over racism, politics, employment, and the community. Using interviews, newspapers, and official UNIA records, this article explains how meaningful this organization was to the growth, security, and well-being of Toronto’s black community.Although this study delves into local history, it is also concerned with transnational relations – primarily, Toronto’s place within the African diaspora. The Toronto Division forged relationships with members around the world while taking part in various UNIA activities that transcended provincial and national boundaries. This article, then, assesses the significance of cross-division cooperation and Toronto’s role in the survival of the Garvey movement in Canada and abroad. Since most members of the UNIA in Toronto were Caribbean immigrants, this essay explores the UNIA’s compatibility with West Indian political and cultural ideals. In this way, this research sets Toronto’s black communities firmly within the African diaspora.